Implementation of the Concept of Circular Economy in Ukraine - Shmygol, Nadia; Galtsova, Olga; Matvejciuk, Liudmyla; Antoniuk, Andrii; Dmytrechenko, Mykyta (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/003, 2021)
The concept of circular economy of Ukraine’s processing industry on the basis of combination of modern practical experience and economic and mathematical methods and models is developed in the work. The concept includes many stages aimed at stabilizing Ukraine’s processing industry in the conditions of transformational changes. Each stage requires appropriate information support, statistical and economic methods of information processing. The decision-making process is based on a scenario approach to modeling, using a modern economic and mathematical apparatus. The relationship between the stages is realized through a system of direct links and feedback, which determine the sequence of management actions. A method of generalizing the index of ecological and economic development has been developed to compare the pace of sectoral development and the amount of damage caused to the environment. Sustainable economic growth in the long run must be ensured by intensive development factors. That is why it is proposed to compare the sectoral index of environmental load with the corresponding index of economic development. In turn, the latter should indicate not only the physical volume of total production at comparable prices, but also reflect the qualitative nature of changes that have occurred during sectoral development, and were associated with a reduction in the share of intermediate consumption. The generalized index of sectoral ecological and economic development thus received will show efficiency of introduction of principles of circular economy in the operation of processing industry companies during the reporting period, and also due to the proposed actions. The economic substantiation of a complex of measures on recycling of the processing sector of Ukraine aimed at maintaining sustainable development is carried out. During 2016-2018, the processing industry created favorable conditions for moderate economic growth, which was accompanied by a reduction in pollution of all kinds. A positive result was achieved due to metallurgical production and mechanical engineering. Since the development and implementation of closed-loop technologies in production activities requires significant investment resources, the recommendations in this case are to maintain existing trends by intensifying environmental measures and further implementing them. It was found that the implementation of measures to minimize the generation of waste within the processing industry only will not be able to radically solve the problem of its generation and accumulation. The solution can only be a comprehensive modernization of the entire economy, in particular, the extractive industry; In the structure of waste use, the largest share, exceeding 70%, was occupied by waste disposal in specially designated areas, and only about 30% accounted for utilization. This situation has developed primarily due to the extraction of iron ore. Areas of possible use of this type of waste are: further processing and extraction of residual minerals at ferrous metallurgy enterprises as building materials of the construction industry. However, given the use of outdated technologies, further processing is not economically feasible. Therefore, in the long run, Ukraine’s industry should reorient from the extraction and primary processing of resources to the production of high-tech products with a high share of added value.